Post-remissional and pre-transplant role of minimal residual disease detected by WT1 in acute myeloid leukemia: A retrospective cohort study. (October 2017) - Frairia, Chiara; Aydin, Semra; Audisio, Ernesta; Riera, Ludovica; Aliberti, Sabrina; Allione, Bernardino; Busca, Alessandro; D'Ardia, Stefano; Dellacasa, Chiara Maria; Demurtas, Anna; Evangelista, Andrea; Ciccone, Giovannino; et al.
Highlights: The role of MRD in acute myeloid leukemia is still under investigation. Baseline WT1 is not associated with response to induction treatment. Patients with post-induction WT1  > 350 had significant reduction of OS and DFS. Pre transplant WT1 was confirmed as an independent risk factor for relapse. WT1 overexpression might represent a MRD tool for risk stratification in AML. Abstract: In acute myeloid leukemia (AML), the detection of minimal residual disease (MRD) is still under investigation. The aim of the present retrospective study was to assess the role of Wilms tumor gene 1 (WT1) overexpression in a large monocentric cohort of AML patients. Among 255 enrolled patients, MRD was investigated in those in complete remission (CR) with an available WT1 at baseline (>250 copies) and at two further time-points: after induction (n = 117) and prior allogeneic hematopoietic cell transplantation (allo-HCT), n = 65. Baseline BM WT1 overexpression was not associated with response to induction (p = 0.244). Median overall survival (OS) and disease-free survival (DFS) were significantly shorter in patients with > 350 WT1 copies after induction compared to those with ≤350 (HR for mortality 2.13; 95% CI 1.14–3.97, p = 0.018 and HR for relapse 2.81; 95% CI 1.14–6.93, p = 0.025). Patients with WT1 > 150 copies pre allo-HCT had a significantly higher 2-year cumulative incidence of relapse (CIR) compared to those with WT1 ≤ 150 (HR 4.61; 95% CI 1.72–12.31, p = 0.002). The prognostic role of WT1 overexpression resulted independent from other well-established risk factors. According to these results, WT1 overexpression might represent an additional MRD tool for risk stratification in patients classified nowadays in CR.